Adsorption of methylene blue and ferrous ion from aqueos solution using coconut husk - Nur Farah Azura, Ab Rahim (2010)
The adsorption process provides an attractive alternative treatment,especially if the adsorbent is inexpensive and readily available.The biomaterials such as coconut husk are low cost agricultural waste residues and are easily available in large quantity in Malaysia.The ability of coconut husk to remove ferum(ii)and Methyene Blue (MB) from aqueous solution as low cost adsorbent was investigated. The adsorption was investigated in three parameters, the effects of the adsorbent dosage, initial concentration and contact time were studied in a batch experiments at room temperature (± 27oC).The coconut husk was dried up at 80oC for 24 hours, and then sieved using sieve shaker.The aqueous solution was mixed with 0.5g adsorbent starting at 100 until 200 minutes with different size of adsorbent in range 500μm to 2mm, while keeping the speed shaker constant at 200RPM. The solution and the adsorbent was separate using filter paper. The same procedure was repeated for initial concentration effect in range 0.25 to 0.05 g/L for FeSO4 and 0.005 to 0.15 g/L for MB,and adsorbent dosage effect in range 2.5 to 5g. Samples of MB and ferum(ii)after the uptake are analyzed with UV-Vis spectrophotometer.Results show that 95.6 - 99.4% of MB removal efficiency was attained in the coconut husk with 500μm of size at 200 minutes of contact time in 0.25g/L of initial concentration. Meanwhile, the removals of ferum (ii)from FeSO4 are 31.2 – 80.8 % respectively.The study is economically feasible and it is proven to be favorable.The results show that coconut husk could be employed effective and low cost material for removal of ferum(ii)and dyes from aqueous solution.